2021
DOI: 10.3389/fcell.2021.715037
|View full text |Cite
|
Sign up to set email alerts
|

The Kinocilia of Cochlear Hair Cells: Structures, Functions, and Diseases

Abstract: Primary cilia are evolutionarily conserved and highly specialized organelles that protrude from cell membranes. Mutations in genes encoding ciliary proteins can cause structural and functional ciliary defects and consequently multiple diseases, collectively termed ciliopathies. The mammalian auditory system is responsible for perceiving external sound stimuli that are ultimately processed in the brain through a series of physical and biochemical reactions. Here we review the structure and function of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In prenatal mice, ACF7 is required for normal kinocilia lengths ( May-Simera and Kelley, 2012 ). Therefore, we tested if kinocilia lengths were altered in P5 Macf1 fl/– ; Pax2-Cre mice, a timepoint during cochlear development that was chosen because it is before the kinocilia degenerate ( Wang and Zhou, 2021 ) but should still also reflect defects in kinocilia formation if they do exist in these conditional knockout animals. Using anti-acetylated tubulin to label the kinocilia and confocal microscope software for measurements, we showed that the mean length of kinocilia from control mice is 2.49 ± 0.02 μm (mean ± SEM) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In prenatal mice, ACF7 is required for normal kinocilia lengths ( May-Simera and Kelley, 2012 ). Therefore, we tested if kinocilia lengths were altered in P5 Macf1 fl/– ; Pax2-Cre mice, a timepoint during cochlear development that was chosen because it is before the kinocilia degenerate ( Wang and Zhou, 2021 ) but should still also reflect defects in kinocilia formation if they do exist in these conditional knockout animals. Using anti-acetylated tubulin to label the kinocilia and confocal microscope software for measurements, we showed that the mean length of kinocilia from control mice is 2.49 ± 0.02 μm (mean ± SEM) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even if kinocilium may present a motile structure (9 + 2), it is considered a nonmotile cilium, lacking inner dynein arms [ 42 ]. Degeneration of kinocilium under maturation of the ear leads to inner and outer hair cells without kinocilia.…”
Section: Genetics Of Ushmentioning
confidence: 99%
“…These tip links are coupled to the mechanosensitive ion channels at the tips of the shorter stereocilia. The longest stereocilia are attached to a microtubule-based protrusion known as kinocilium [302]. Mechanical tension generated in the tip links by deflection of the bundle of stereocilia results in the opening of the ion channels thereby triggering mechano-electrical transduction.…”
Section: Stereociliamentioning
confidence: 99%